The Australian East-West Radio Relay System Revisited - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2024)
The Journal revisits an historic paper from 1971 by R. W. Richards and J. Donovan of GEC-AEI Telecommunications on the prime contractor’s role in the delivery of the Australian East-West radio relay system from Northam in Western Australia to Port Pirie in South Australia.